1993
DOI: 10.2307/2939202
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Determine Prevalence of Use of Contraceptive Methods for Men

Abstract: Globally, men have not shared equally with women the responsibility for fertility regulation. While family planning efforts have been directed almost exclusively toward women, the lack of male involvement may also reflect the limited options available to men. Current methods for men are either coitus-dependent, such as the condom or withdrawal, or permanent, such as vasectomy. The 20-year history of social science research on male contraceptive methods is examined here in terms of the human and method factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 48 publications
3
43
0
5
Order By: Relevance
“…Although these similar reasons were reported for non-approval of contraception in some studies 16,17,18 , the desire for more children (particularly sons) has been identified as a significant factor in the negative attitude to contraception. In many African societies, males are valued more highly than females and therefore couples tend to aim for the birth and survival of at least a son 19,20 . This is particularly pronounced in the traditional societies where sons are needed to maintain the family lineage, assist the family economically and provide parents with social security in old age 21,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although these similar reasons were reported for non-approval of contraception in some studies 16,17,18 , the desire for more children (particularly sons) has been identified as a significant factor in the negative attitude to contraception. In many African societies, males are valued more highly than females and therefore couples tend to aim for the birth and survival of at least a son 19,20 . This is particularly pronounced in the traditional societies where sons are needed to maintain the family lineage, assist the family economically and provide parents with social security in old age 21,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Glasier et al [24] the majority of men responding to a survey, believed that they should be more responsible for contraception than they were. It has also been asserted that a high proportion of men from developed as well as developing countries are prepared to use a hormonal method once it is made available [32]. This shared responsibility was also demonstrated by Oudshoorn [17], who quotes one of the men in Ringheim"s study: "If she goes on the Pill again there is always the risk, isn"t it?…”
Section: Perceptions Of Contraceptive Responsibilitymentioning
confidence: 98%
“…It seems like the abnormal rather than the normal, the idea that the bloke, apart from condoms, would actually take any part of sexual responsibility for contraception, particularly not one which involved needles" [32]. These quotes from qualitative studies are powerful examples of how stereotypes influence male attitudes, with many choosing to reject new forms of male contraception in favour of safeguarding their masculinity.…”
Section: Fear Of Losing Connotations Of Masculinitymentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of certain successful methods on females, most of the burdens of contraceptive are now on women, thus taking men out from the sphere of contraceptive. Globally, men have not shared the responsibility equally with women for fertility regulation, the lack of male involvement may also reflect the limited options available to men (Ringheim, 1993). It has been observed that fewer than half of men aged 25 to 39 years in union do discuss family planning with their wife or partner in much of sub-Saharan Africa, Pakistan and in Egypt (TAGI, 2003).…”
Section: Introductionmentioning
confidence: 99%